Partners in Crime in the Setting of Recurring Cardiac Arrest - Lida P. Papavasileiou; Giovanni B. Forleo; Luca Santini; Eugenio Martuscelli; Francesco Romeo (Cardiology Research and Practice)
No previous reports are available about the potential dramatic effects resulting from the combination of acquired long QT interval not associated to bradycardia and myocardial ischemia. We report the case of a man that during acute necrotic pancreatitis presented QT interval prolongation without bradycardia, TdP, and two episodes of cardiac arrest. A coronary angiogram revealed a subocclusive stenosis of left anterior descending coronary artery, treated with a percutaneous coronary intervention. After myocardial revascularization, even in presence of long QT interval, no arrhythmic events occurred suggesting the key role of myocardial ischemia in triggering TdP in acquired long QT even without bradycardia. ECG performed six months later, after complete recovery from pancreatitis, showed a normal QT interval.